Forecast modeling of foreign trade in agricultural complex products between Ukraine and Romania - Totska, Olesia Leontiivna (My University, 2022)
The article presents forecast modeling of foreign trade between Ukraine and Romania by separate groups of agro-industrial goods. Indicators were forecast for three years (2022-2024) based on actual data for eleven years (2011-2021). Five trend models (exponential, linear, logarithmic, polynomial, and power) were constructed for each indicator and only one with the highest value of the reliability of the approximation R² was selected. The constructed trend models indicate a positive trend in 2022-2024 for preparations of grains, cocoa and cocoa preparations, sugar and sugar confectionery, animal or plant fats and oils; in 2023-2024 – for meat and meat preparations, alcoholic and non-alcoholic beverages, vinegar. At the same time, the forecast models indicate an increase in imports of tobacco and its industrial substitutes in 2023-2024, a decrease in imports of cereals over the same period, an increase in imports of other mixed foodstuffs in 2022-2024. Of the nine selected models, six are polynomial, one is power, one is logarithmic, and one is exponential. Two of them have a very high degree of reliability of the approximation R² (>0.9) and, accordingly, a high probability of forecast prediction.

У статті здійснено прогнозне моделювання зовнішньої торгівлі між Україною та Румунією окремими групами товарів агропромислового комплексу. Прогнозування показників проводилося на три роки (2022–2024) на основі фактичних даних за одинадцять років (2011–2021). Для кожного показника було побудовано п’ять трендових моделей (експоненційну, лінійну, логарифмічну, поліноміальну та степеневу) й обрано тільки одну з найбільшою величиною достовірності апроксимації R². Побудовані трендові моделі вказують на позитивну динаміку у 2022-2024 рр. для готових продуктів із зерна, какао та продуктів із нього, цукру та кондитерських виробів із цукру, жирів та олії тваринного або рослинного походження; у 2023-2024 рр. – для м’яса та їстівних субпродуктів, алкогольних і безалкогольних напоїв та оцту. Водночас прогнозні моделі вказують на зростання імпорту тютюну та його промислових замінників у 2023-2024 рр., зниження імпорту зернових культур за цей же період, зростання імпорту різних харчових продуктів у 2022-2024 рр. Із дев’яти побудованих моделей шість – поліноміальних, одна – степенева, одна – логарифмічна, одна – експоненційна. Дві з них мають дуже високий ступінь достовірності апроксимації R² (>0,9) та, відповідно, високу імовірність справдження прогнозу.
Keywords: forecast modeling; foreign trade; products of the agro-industrial complex; Ukraine; Romania